Isolation and Analysis of Phanera variegata Mucilage by Various Analytical Techniques - Bansal, Keshav; Bajpai, Meenakshi (Indian Journal of Pharmaceutical Education and Research, 2024)
Objectives: The objective of the present study was to isolate mucilage from the leaves of Phanera variegata L., to do the thermal, microscopic, elemental analysis, and physicochemical characterization of isolated mucilage. The various analytical methods were applied to mucilage and evaluated its nature, thermal stability, and structure. Materials and Methods: The mucilage was isolated and analyzed by various analytical methods like SEM, PXRD, particle size analysis, DSC, TGA, elemental analysis (CHNS), zeta potential, FTIR, and 1D (1H and 13C) NMR spectroscopy. Results: The SEM analysis indicated that mucilage particles had irregular shapes and sizes. The PSA indicated that particles of mucilage had a particle size of nanometers. The DSC analysis observed the mucilage's glass Transitional temperature (Tg) at 95.9ºC. The TGA analysis suggested the three-stage decomposition with the good thermal stability of mucilage. A complete amorphous nature of the mucilage was indicated by PXRD analysis. The specific content of CHNS was revealed by elemental analysis. FT-IR spectra identified the major functional groups include 3240 cm-1(-OH), 2848 cm-1(C-H), 1599 cm-1(C-OH), 1419 cm-1(-COO-), 1253 cm-1(C-O). 1D Hydrogen-1 and Carbon-13 NMR confirmed the presence of polysaccharides that have many similar sugar residues. Conclusion: The P. variegata mucilage was found amorphous, thermally stable, and can be used as an excellent alternative natural pharmaceutical excipient for conventional pharmaceutical drug products and novel drug delivery systems in varying concentrations.
Keywords: Phanera variegata; Pharmaceutical excipients; Mucilage; Microscopic analysis; Elemental analysis; Structure analysis